2008
DOI: 10.1159/000121339
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Aggregation and Recruitment with Aspirin-Clopidogrel Therapy

Abstract: Background: Aspirin-clopidogrel combination therapy inhibits platelet aggregation. The effect on platelet recruitment is unknown. Methods: Thirty chronic ischemic stroke patients taking aspirin alone followed by aspirin-clopidogrel combined therapy had platelet reactivity tests performed over 3 months: ex vivo platelet aggregation, platelet recruitment and urinary 11-dehydro-thromboxane B2 (11-dhTxB2)excretion. Statistical analysis of variance compared platelet aggregation and recruitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…This may be due to already low thromboxane generation in healthy subjects in contrast to patients with manifest vascular disease where thromboxane generation is increased [4,55]. However, Helgasson et al had similar negative findings as ours in a study in 30 chronic ischemic stroke patients treated with aspirin and clopidogrel [226]. It has recently been proposed that aspirin may provide little additional protection against athero-thrombotic events in presence of strong P2Y 12 receptor blockade [227], but this is speculative since no large study has investigated the effect of adding aspirin or placebo to clopidogrel treatment in patients with CAD.…”
Section: Discussionsupporting
confidence: 54%
“…This may be due to already low thromboxane generation in healthy subjects in contrast to patients with manifest vascular disease where thromboxane generation is increased [4,55]. However, Helgasson et al had similar negative findings as ours in a study in 30 chronic ischemic stroke patients treated with aspirin and clopidogrel [226]. It has recently been proposed that aspirin may provide little additional protection against athero-thrombotic events in presence of strong P2Y 12 receptor blockade [227], but this is speculative since no large study has investigated the effect of adding aspirin or placebo to clopidogrel treatment in patients with CAD.…”
Section: Discussionsupporting
confidence: 54%
“…1) [10,12,13,14,15,22,23,24]. A total of 18 studies were excluded: four were excluded because they were not RCTs [25,26,27,28], three were excluded because the comparator was not aspirin or clopidogrel alone [29,30,31], seven were excluded for lack of specific data [9,32,33,34,35,36,37], two were excluded since the trials were ongoing [38,39], and two were excluded due to redundancy [40,41]: the original study reported both primary and secondary prevention, and the subsequent report [14] focused on results in patients with previous TIA or ischemic stroke. The baseline characteristics of included studies are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…PST carries out this type of projection by means of an evolutionary algorithm called GenD [ 3 ], specifically defined to achieve this aim. Pilot experiences in medicine are already available and seem quite encouraging [ 4 , 5 ].…”
Section: Editorialmentioning
confidence: 99%